2020
DOI: 10.1136/oemed-2019-106375
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb venous and arterial peripheral diseases and work conditions: systematic review

Abstract: ObjectivesThe individual peripheral vascular disease risk factors are well documented, but the role of work conditions remains equivocal. This systematic review aims to assess relationships between lower limb peripheral venous diseases (lower limb varicose veins (LLVV), venous thromboembolism (VTE) comprising deep vein thrombosis and pulmonary embolism), peripheral arterial disease (intermittent claudication, aortic dissection, aortic aneurysm) and occupational constraints among working adults.MethodsSeveral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…In literature, standing for long periods is the most mentioned risk factor for VV (17,37,(39)(40)(41)(42). In the current study, the duration of standing for 4 hours or more was significantly associated with a higher prevalence of VV.…”
Section: Vv Risk Factorssupporting
confidence: 55%
See 2 more Smart Citations
“…In literature, standing for long periods is the most mentioned risk factor for VV (17,37,(39)(40)(41)(42). In the current study, the duration of standing for 4 hours or more was significantly associated with a higher prevalence of VV.…”
Section: Vv Risk Factorssupporting
confidence: 55%
“…They should be informed about the negative consequences of improper use of topical corticosteroids, including disease relapse and the occurrence of unfavorable adverse effects (40). They should be informed about the importance of topical corticosteroid maintenance therapy to minimize flare-ups or relapses (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] A systematic review reported that workers who stood longer than 3-4 hours per day seemed to have an increased risk (~2.5-fold higher) of LLVV than those who were less exposed. 24 Several studies reported that women had higher prevalence 23 or risk (workers with prolonged standing vs no prolonged standing) than men. 25 Given that our reference group was the general population in which the above-mentioned occupational types had the same characteristic of prolonged standing as the FBSI workers, this might explain why female FBSI workers did not show an increased risk of peripheral vascular diseases, while male FBSI workers tended to experience prolonged standing and thus had higher risk of peripheral vascular diseases than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that between 15–30% of all cases of venous thromboembolic disease may be due to recreational or occupational immobility. 8 , 9 , 10 …”
mentioning
confidence: 99%